Negative gearing reforms could save A$1.7 billion without hurting poorer investors - Hodgson, Helen; Duncan, A.; ViforJ, R.; Minas, J. (The Conversation, 2018)
New modelling shows negative gearing and capital gains taxes can be reformed in a way that doesn't impact poorer investors.